USE OF AUTOLOGICAL PLATE-RICH PLASMA IN TREATMENT OF GONARTHROSIS (Euro-Asia Conferences, 2021)
Gonarthrosis (GA) is a chronic progressive degenerative joint diseasecharacterized by degradation of articular cartilage followed by changes inthe subarochnoid bone and the development of marginal osteophytes. Thesechanges lead to the loss of cartilage and concomitant damage to othercomponents of the joint (synovium, ligaments). GA was considered for along time as a disease of articular cartilage, but today there is evidence that,in addition to articular cartilage, other anatomical structures of the joint arealso involved in the pathological process: capsule, meniscus, subchondralbone, as well as muscles and ligaments.